1993
DOI: 10.1128/mcb.13.9.5461
|View full text |Cite
|
Sign up to set email alerts
|

Control of BEK and K-SAM splice sites in alternative splicing of the fibroblast growth factor receptor 2 pre-mRNA.

Abstract: The fibroblast growth factor receptor 2 gene pre-mRNA can be spliced by using either the K-SAM exon or the BEK exon. The exon chosen has a profound influence on the ligand-binding specificity of the receptor obtained. Cells make a choice between the two alternative exons by controlling use of both exons. Using fibroblast growth factor receptor 2 minigenes, we have shown that in cells normally using the K-SAM exon, the BEK exon is not used efficiently even in the absence of the K-SAM exon. This is because these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 39 publications
5
57
1
Order By: Relevance
“…The IIIa splice variant yields a secreted FGF receptor that is derived of any signaling capacity. The expression of the IIIb splice variant is believed to be restricted to epithelial cell types whereas the expression of the IIIc splice variant is believed to be restricted expressed to mesenchymal cell types (Avivi et al, 1993;Gilbert et al, 1993;Orr-Urtreger et al, 1993;Yan et al, 1993;Alarid et al, 1994). Surprisingly, in the present study we found that COLO-357 cells express the IIIc splice variant of FGFR-1, but the IIIb variant of FGFR-2.…”
Section: Discussioncontrasting
confidence: 76%
“…The IIIa splice variant yields a secreted FGF receptor that is derived of any signaling capacity. The expression of the IIIb splice variant is believed to be restricted to epithelial cell types whereas the expression of the IIIc splice variant is believed to be restricted expressed to mesenchymal cell types (Avivi et al, 1993;Gilbert et al, 1993;Orr-Urtreger et al, 1993;Yan et al, 1993;Alarid et al, 1994). Surprisingly, in the present study we found that COLO-357 cells express the IIIc splice variant of FGFR-1, but the IIIb variant of FGFR-2.…”
Section: Discussioncontrasting
confidence: 76%
“…These observations suggest that the dorsoventral gradients of the FGFR2 variants in both embryonic development and limb regeneration are governed by the same homeotic genes. Interestingly, Gilbert et al (1993) showed, using FGFR2 minigenes, that cells normally using exon IIIb apparently express a titratable repressor which excludes the splicing of exon IIIc. It was further proposed that in the absence of the repressor, exon IIIc is preferred over exon IIIb due to the three purines in the exon IIIb poly- These are adjacent sections taken from the same limb.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that some cells still expressed a mesenchymal phenotype after 4 d of KGF treatment ( Figures 1B and 8B) can probably be explained by the relative heterogeneity of the NBT-II cells. As seen in Figure 7 and Figure 8, the RNA switch is not total, and some cells probably express enough FGFR2b/KGFR to remain induced and maintain (Gilbert et al, 1993). During embryonic development, a linkage between FGFR expression and differentiation process involving phenotype transition may also occur.…”
Section: Modulation Of Dna Synthesis In Fgfr-transfected Cellsmentioning
confidence: 99%